Multidisciplinary approach and treatment of acral and mucosal melanoma - Fortuna, Ana; Amaral, Teresa (Frontiers in Oncology, 2024)
Acral and mucosal melanoma are uncommon variants of melanoma. Acral melanoma has an ageadjusted incidence of approximately 1.8 cases per million individuals per year, accounting for about 2% to 3% of all melanoma cases. On the other hand, mucosal melanoma, with an incidence of 2.2 cases per million per year, makes up around 1.3% of all melanoma cases. These melanomas, in addition to being biologically and clinically distinct from cutaneous melanoma, share certain clinical and pathologic characteristics. These include a more aggressive nature and a less favorable prognosis. Furthermore, they exhibit a different mutational pattern, with KIT mutations being more prevalent in acral and mucosal melanomas. This divergence in mutational patterns may partially account for the relatively poorer prognosis, particularly to immune checkpoint inhibitors.This review explores various aspects of acral and mucosal melanoma, including their clinical presentation, pathologic features, mutational profiles, current therapeutic approaches, outcomes associated with systemic therapy, and potential strategies to address resistance to existing treatments.